Penanaman Nilai Budi Pekerti melalui Aktivitas Bermain Peran Anak Usia Dini - Siti Istatik Choiroyaroh (Kartika: Jurnal Studi Keislaman, 2026)
This study aims to analyze the inculcation of moral values in early childhood through role-playing activities. The research employs a qualitative approach using a library research method by reviewing various scholarly sources related to character education, child development, and play-based learning strategies. Data were analyzed using content analysis through data reduction, data display, and conclusion drawing techniques. The findings indicate that moral values such as honesty, responsibility, discipline, politeness, cooperation, and social care can be effectively developed through role-playing activities. This method enables children to learn through direct experiences in social situations that are close to their daily lives. In addition, teachers play a crucial role as role models, facilitators, and guides in creating meaningful learning experiences. Role-playing integrates cognitive, social, and moral aspects of child development simultaneously. The novelty of this study lies in the integration of moral development theory, social learning theory, and early childhood pedagogical approaches into a comprehensive analytical framework. Therefore, role-playing is an effective strategy for character building in early childhood education